2022
DOI: 10.1099/ijsem.0.005453
|View full text |Cite
|
Sign up to set email alerts
|

International Committee on Systematics of Prokaryotes, Subcommittee on the taxonomy of Rhizobia and Agrobacteria, minutes of the annual meeting by videoconference, 5 July 2021, followed by online discussion until 31 December 2021

Abstract: Minutes of the closed meeting of the International Committee on Systematics of Prokaryotes Subcommittee on the Taxonomy of Rhizobia and Agrobacteria held by videoconference, 5 July 2021, followed by online discussion until 31 December 2021, and list of recent species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…We discussed the recent paper published by Ma et al [3], who reported an extensive genome-based taxonomic revision of the family Rhizobiaceae with proposals at two levels (species and genus) that will presumably be submitted to the IJSEM for validation. The research and results cover much of the ground of Action Point 8.1 (Minute 8) of our previous meeting [1], which was implemented by P. Young, G.C. diCenzo and N. Kuzmanović.…”
Section: Minute 10 Revision Of the Genus Rhizobium And Following Up T...mentioning
confidence: 97%
See 4 more Smart Citations
“…We discussed the recent paper published by Ma et al [3], who reported an extensive genome-based taxonomic revision of the family Rhizobiaceae with proposals at two levels (species and genus) that will presumably be submitted to the IJSEM for validation. The research and results cover much of the ground of Action Point 8.1 (Minute 8) of our previous meeting [1], which was implemented by P. Young, G.C. diCenzo and N. Kuzmanović.…”
Section: Minute 10 Revision Of the Genus Rhizobium And Following Up T...mentioning
confidence: 97%
“…The Executive Board of the ICSP (EB-ICSP) asked us, in a letter from the Secretary for Subcommittees, Professor Stephen On, dated 26 September 2023 and Minute 9 of EB-ICSP meeting on 31 August 2023 (www.the-icsp.org/images/minutes/20230928_ EB-ICSP_Meeting-20230831%20-%20Minutes.pdf), to clarify some aspects of Minute 10 of the 2022 Subcommittee meeting [1]. After discussion, the following statements were approved.…”
Section: Minute 6 Response To Letter From Icsp Secretary For Subcommi...mentioning
confidence: 99%
See 3 more Smart Citations